1994
DOI: 10.1073/pnas.91.26.12428
|View full text |Cite
|
Sign up to set email alerts
|

Expression of apple 1-aminocyclopropane-1-carboxylate synthase in Escherichia coli: kinetic characterization of wild-type and active-site mutant forms.

Abstract: The pyridoxal phosphate-dependent enzyme 1-aminocyclopropane-l-carboxylate synthase (ACC synthase; S-adenosyl-L-methionine methylthioadenosine-lyase, EC 4.4.1.14) catalyzes the conversion of S-adenosylmethionine (AdoMet) to ACC and 5'-methylthioadenosine, the committed step in ethylene biosynthesis in plants. Apple

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 32 publications
4
76
0
Order By: Relevance
“…Kinetic Characterization of ACC Synthase Inactivation by AVG-ACC synthase activity in the presence of AVG was monitored by a continuous coupled assay (14). Reactions were initiated by the addition of ACC synthase to mixtures of AVG, SAM, and coupling enzyme preequilibrated in buffer at 25°C.…”
Section: Methodsmentioning
confidence: 99%
“…Kinetic Characterization of ACC Synthase Inactivation by AVG-ACC synthase activity in the presence of AVG was monitored by a continuous coupled assay (14). Reactions were initiated by the addition of ACC synthase to mixtures of AVG, SAM, and coupling enzyme preequilibrated in buffer at 25°C.…”
Section: Methodsmentioning
confidence: 99%
“…In aspartate aminotransferase and 1-aminocyclopropane-1-carboxylate synthase, the phenolic oxygen interacts with a tyrosine residue (14,15). The deletion of the hydrogen bond through the replacement of the active site tyrosine with phenylalanine reveals a different function in the kinetic properties of each enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…The AdoMet used in the enzyme assay which contained 59% of (S,S) diastereomer form [9] was purchased from Boerhinger-Mannheim Biochem (Germany). ACC synthase activity was assayed by incubating the crude (5-15 pg) or the highly purified (0.3 pg) ACC synthase extract with AdoMet at 30°C for 30 min in a reaction buffer containing 25 mM HEPES at pH 8.5, 10 pM PLP and 1 mM DTT.…”
Section: N-terminal Deletion Nestmentioning
confidence: 99%
“…SSD1 0014-5793(95)01464-0 On optimum alignment of ACC synthase amino acid sequences, it was found that there were seven highly conserved regions [6] and 16 invariant amino acid residues [9] in this enzyme. The overall amino acid sequences are 72-81% similar and 53-67% identical with the exception of the amino-and, particularly, the carboxyl-termini of ACC synthase which were found to be highly variable in both length and primary sequence [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation